Analisis Alokasi Biaya Bersama ddengan Menggunakan Metode Nilai Jual Relatif Pada Usaha Martabak Manis - Rahma; Rahmadani, Rahmadani; Aini, Putri (Jurnal Akuntansi, Manajemen, Bisnis dan Teknologi, 2023)
This study aims to prove how the process of allocating shared costs in the sweet martabak business on Jalan Pintu Air IV, Kwala Bekala, Medan Johor District, Medan. Data collection techniques used observation and interview methods. Researchers made direct observations of financial recording methods at the Sweet Martabak Business on Jalan Pintu Air IV Kwala Bekala. The result of this study is that sweet martabak businesses do not calculate in detail and do not use special methods to calculate joint cost allocation for sweet martabak. Through joint costs using the relative selling price method, the business has an allocation of joint costs of IDR 5,004,500 with a gross profit of IDR 2,273,500. The selling price method is the most appropriate method because this method has the advantage that the selling price can reflect the amount of costs absorbed by each type of product produced.